Basic and complex emotion recognition in children with autism: cross-cultural findings - Fridenson-Hayo, Shimrit; Bölte, Sven (Molecular autism, 2016)
Children with autism spectrum conditions (ASC) have emotion recognition deficits when tested in different expression modalities (face, voice, body). However, these findings usually focus on basic emotions, using one or two expression modalities. In addition, cultural similarities and differences in emotion recognition patterns in children with ASC have not been explored before. The current study examined the similarities and differences in the recognition of basic and complex emotions by children with ASC and typically developing (TD) controls across three cultures: Israel, Britain, and Sweden.
Gesehen am 31.10.2019